Understanding the Expressions of Power and Its Effect on Socioeconomic Outcomes of DIDR Projects - Royal Aliu, Oluwafemi; Olamide Aliu, Iyanuoluwa; Babawole Familusi, Olayemi (Management Analytics and Social Insights, 2025)
The ability of one actor to influence the behavior or dispositions of other agents is power. Furthermore, the type of power that interests social and political scientists the most is social ability, meaning that an agent's power stems from her social position rather than just her unique physiological and psychological characteristics. It is common to assume that power, in this socially mediated sense, has a broad function in social explanations. For instance, social scientists utilize the idea to explain how social institutions are created, maintained, and altered, how individuals behave, and how social interactions turn out. Insofar as the lack thereof affects these clarifications, power has an explanatory function. More controversially, others believe power is a causative component that may help explain various social events since it is usually independent in a given context. Power is not always understood as a context-independent variable by those who write about it or use it. The aim of this study is to explore the expressions of power and its effect on socioeconomic outcomes of Displacement-Induced Development and Resettlement (DIDR) projects, with a view to delve into how power is understood in development studies; the expressions of power in development studies; and how the socioeconomic outcome of DIDR projects is affected by power.